Lumbosacral Malignant Peripheral Nerve Sheath Tumor in a French Bulldog - Sanches da Silva, Paloma Helena; Ferry de Souza, Erick; Dornas de Oliveira Pereira, Renato; de Pádua Costa, Mariana; Dantas Cassali, Geovanni; Pinheiro Fantinatti, Alexandra; José Faváro, Wagner; dos Santos Horta, Rodrigo (Acta Scientiae Veterinariae, 2024)
Background: Benign or malignant peripheral nerve sheath tumors originate from Schwann cells and the connective tissue that surrounds the nerve bundles. Malignant peripheral nerve sheath tumors are highly recurrent, despite its relative low metastatic potential. Although frequently diagnosed in the subcutaneous tissue, those tumours are rarely reported within nerve roots (somatic and autonomous), cranial or spinal nerves and its extensions but are considered the main neoplasms from the peripheral nervous system. Clinical signs observed will vary according to the neurolocation and degree of tumour compression and the presumptive diagnosis can be based on the clinical characteristics and complementary tests such as radiography, myelography, computed tomography and especially magnetic resonance imaging for the excellent resolution of soft tissues. Tumor location at the brachial and lumbosacral plexus poses challenges in the diagnostic and therapeutic approach, mainly due to the impossibility of complete resection, which results in a poor prognosis, also considering the chemoresistance and radioresistance intrinsic to this histopathological type. There is limited evidence for chemotherapy at maximum tolerated dose or metronomic. Among new therapeutic strategies in veterinary oncology, immunotherapy stands out due to its relevant influence on the tumor microenvironment, being one of the innovative therapy modalities that have been developed in recent decades to treat cancer. Case: This study aimed to report the challenges faced in the diagnostic and therapeutic approach of a 12-year-old French Bulldog with a malignant peripheral nerve sheath tumor in the lumbosacral region, treated with decompressive surgery, adjuvant chemotherapy at maximum tolerated dose, metronomic chemotherapy and OncoTherad® nanoimmunotherapy. Disease progression occurred 5 months after surgery and the dog developed lung metastasis despite the efforts for its diagnosis, staging and treatment. Discussion: Peripheral nerve sheath tumors malignant can arise from spinal nerves, primarily in the brachial and lumbosacral plexus and their roots, but also from cranial nerves. In the patient’s CT scan, the presence of soft density extradural neoformation was detected occupying more than half of the vertebral canal and compromising the cauda equina at the lumbosacral junction, thus corroborating the information found in the literature. The tumour was deemed unresectable, but surgery was performed for alleviating compression of the nerve roots and diagnosis. The definitive diagnosis can be reached by the histopathological examination performed in the presented case, after decompression surgery. For further characterization of the neoplasm, an immunohistochemical panel was performed, which confirmed the mesenchymal and neural origin, thus confirming neurofibrosarcoma. The prognosis was poor due to the involvement of nerve roots, psoas muscle and extradural canal affected by the neoplasm. Complete resection was impossible, resulting in permanence of macroscopic disease and also increasing the chances of local progression, which occurred 5 months after surgery despite multimodal treatment. Palliative care was performed as an attempt to assure quality of life and prolong life expectation including anti-inflammatory, analgesics, metronomic chemotherapy and immunotherapy with OncoTherad®. Keywords: peripheral nervous system, soft tissue sarcoma, oncology, immunotherapy, spinal decompression.